A programmable dirham coin based Hajj saving electronic device - Wan Nordin, Mimi Aminah; Aibinu, Abiodun Musa; Arai, Saima (2010)
Hajj, one of the five pillars of religion of Islam requires long-term saving. As most of the Muslim majority countries are developing countries and also facing financial instabilities, savings tend to loose value due to depreciation of the national currencies, political and economic conditions of the countries. As a solution to this problem, hajj saving in gold has been proposed has the solution to this paper money devaluation. Previous studies have proven that there is a significant effect in cost of hajj when it is priced in gold oppose to paper currency.